Rapid Detection Of Methicillin Resistant Staphylococci Using Multiplex PCR With Boiling Method For DNA Isolation - Wibawa, Ida Bagus Gede Adiguna; Darwinata, Agus Eka; Fatmawati, Ni Nengah Dwi; Budayanti, Nyoman Sri (Journal of Health Sciences and Medicine, 2018)
Methicillin-Resistant Staphylococcus aureus   (MRSA) is Staphylococcus aureus   that has become insusceptible or resistant by methicillin antibiotic types. Rapid identification of MRSA is essential for early initiation of appropriate antimicrobial therapy. The aim of this research is to reduce the cost and time needed for multiplex PCR in rapid detection of MRSA by finding an alternative method for DNA which is boiling method. DNA isolation was performed with boiling method and kit commercial. The kit method takes time approximately 45 minutes while boiling takes only about 12 minutes. PCR result with boiling technique used in DNA isolation formed amplification bands of 16S rRNA, mecA , and nuc   in MRSA and 16S rRNA and nuc   in MSSA. Conclusion can be drawn that boiling method can be used as an alternative method for DNA extraction.